2016
DOI: 10.1289/ehp.1307736
|View full text |Cite
|
Sign up to set email alerts
|

Vehicular Traffic–Related Polycyclic Aromatic Hydrocarbon Exposure and Breast Cancer Incidence: The Long Island Breast Cancer Study Project (LIBCSP)

Abstract: BackgroundPolycyclic aromatic hydrocarbons (PAHs) are widespread environmental pollutants, known human lung carcinogens, and potent mammary carcinogens in laboratory animals. However, the association between PAHs and breast cancer in women is unclear. Vehicular traffic is a major ambient source of PAH exposure.ObjectivesOur study aim was to evaluate the association between residential exposure to vehicular traffic and breast cancer incidence.MethodsResidential histories of 1,508 participants with breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 51 publications
6
80
1
Order By: Relevance
“…This is consistent with the positive association between exposure to polycyclic aromatic hydrocarbons from car traffic and BC incidence, reported by the Long Island Breast Cancer Study. 24 The authors of the Taiwan study concluded that particle-induced ROS formation contributed to oxidative DNA damage that may mediate particle-induced carcinogenesis. 23 The finding that particles have oestrogenic and DNA-damaging effects suggests a potential mechanism for an effect on BC: if inhaled PM entered the circulatory system from the lungs, oestrogenic particles might find their way to breast tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the positive association between exposure to polycyclic aromatic hydrocarbons from car traffic and BC incidence, reported by the Long Island Breast Cancer Study. 24 The authors of the Taiwan study concluded that particle-induced ROS formation contributed to oxidative DNA damage that may mediate particle-induced carcinogenesis. 23 The finding that particles have oestrogenic and DNA-damaging effects suggests a potential mechanism for an effect on BC: if inhaled PM entered the circulatory system from the lungs, oestrogenic particles might find their way to breast tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies examining air pollution exposure and breast cancer risk reported mixed results, one with no association,11 while the other found a positive association 12. However, the majority of studies to date focused on ambient air pollution, smoking and other sources that confer exposure that is, compared with PAH-contaminated workplaces,13–18 much lower in intensity.…”
Section: Introductionmentioning
confidence: 99%
“…PAH exposure has also been linked to respiratory distress in asthmatic children (Gale et al 2012). Chronic exposure in adults has been linked to the development of breast, lung, gastrointestinal, and bladder cancers (Armstrong, Hutchinson, Unwin, and Fletcher 2004; Bosetti et al 2007; Mastrangelo, Fadda, and Marzia 1996; Mordukhovich et al 2016; Zhang et al 2016). Although the majority of studies investigating PAH-associated cancers have focused on occupational exposures (Bosetti et al 2007), a growing body of evidence has highlighted the need for additional research in residential settings (DellaVale et al 2016; Deziel et al 2014; Kang et al 2015).…”
Section: Introductionmentioning
confidence: 99%